The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.ejso.2013.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and female sexual function after skinning vulvectomy with split-thickness skin graft in women with vulvar intraepithelial neoplasia or vulvar Paget disease

Abstract: Skinning vulvectomy with split-thickness skin graft is a feasible technique yielding good results in terms of quality of life and sexual function. It enables occult cancer to be diagnosed in patients with VIN or Paget disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 35 publications
(35 reference statements)
0
6
1
Order By: Relevance
“…27 However, in the two studies that reported total FSFI scores in vulvar cancer patients, these scores were higher than in our study group. 21,25 Also, the total FSFI scores and all subdomains of our study group were worse than those of healthy Dutch women reported by Ter Kuile et al 14 (mean 17.1 vs 31.2). However, the women reported by Ter Kuile et al 14 are younger in our study group (mean age 65.5 vs 27.1 years).…”
Section: Sexual Functioningcontrasting
confidence: 61%
“…27 However, in the two studies that reported total FSFI scores in vulvar cancer patients, these scores were higher than in our study group. 21,25 Also, the total FSFI scores and all subdomains of our study group were worse than those of healthy Dutch women reported by Ter Kuile et al 14 (mean 17.1 vs 31.2). However, the women reported by Ter Kuile et al 14 are younger in our study group (mean age 65.5 vs 27.1 years).…”
Section: Sexual Functioningcontrasting
confidence: 61%
“…Some of the limitations of the present study include the small size of the study group, its design as a retrospective study, the low cost‐effectiveness of the treatment, and the risk of missing occult microinvasive cancer . Indeed, the procedure of PDT and the PSZs were not covered by public insurance in Korea.…”
Section: Discussionmentioning
confidence: 97%
“…Currently, the incidence of VIN is increasing in developed countries, and the disease is mainly affecting young women . Radical surgery for the treatment of these diseases is too extensive; while destructive surgery results in a good prognosis, its consequences can also include genital mutilation and disfiguration, sexual dysfunction, and psychosocial problems for patients . The preservation of normal genital anatomy and function is of importance to patients.…”
Section: Introductionmentioning
confidence: 99%
“…The goals of reconstruction are to preserve the vaginal and urethral introitus, prevent delays in adjuvant treatment, and minimize donor site morbidity. Numerous techniques have been described in the literature, including healing by secondary intention, skin grafts, and locoregional flaps (Dias‐Jr et al, 2019; Galandiuk, Jorden, Mahid, McCafferty, & Tobin, 2005; Hage, Lange, Zijlmans, & van Beurden, 2018; Hand et al, 2018; Hashimoto, Abe, & Nakanishi, 2014; Hollenbeck et al, 2011; Lavoué et al, 2013; Mercut et al, 2018; Stephanie et al, 2019; Tan, Kang, Tay, & Por, 2014). Many of these options require well‐vascularized recipient or donor site tissues, which is often not the case in patients who have had prior radiation and surgical therapy.…”
Section: Introductionmentioning
confidence: 99%